The Risks of Innovation: Are Innovating Firms Less Likely to Die? - Fernandes, Ana M.; Paunov, Caroline (The Review of Economics and Statistics, 2015)
While innovation matters for competitiveness, it may expose firms to survival risks. Using plant-product data for Chile and discretetime hazard models, we show that innovating plants have a lower hazard of exit. However, risk has a strong impact on the innovation-exit relationship: only innovators that retain diversified sources of revenue or face lower market risk are less likely to die. Single-product innovators are at greater risk of exiting. Exposure to technical risk does not affect exit probabilities differentially. We provide tentative evidence that singleproduct innovators have higher profits, which helps to rationalize their innovation decision despite the increased risk of exit.